Niẓām al-Mulk dan Kontribusinya terhadap Pemikiran Politik Islam - Ahmad Nur Fuad (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2018)
This article seeks to explore Niẓām al-Mulk’s political career and his contribution to Islamic political thought. As a prominent wazīr of two Seljuq sultans, Alp Arslan and Malikshah, Niẓām al-Mulk played an important role in running the government for almost 30 years. His adherence to Sunni theological doctrines and Shafi'i school of law has made him a defender of Sunnism against other sects like Ismailism. As a political figure and thinker, Niẓām al-Mulk regarded justice and religion as a fundamental basis for the state. In Siyāsat-nāma, he elaborates many political bodies needed to build a strong state and government, such as wazīr, qādī, tax collectors, military, and intelligent agency. It can be argued that Niẓām al-Mulk’s political thought as formulated in his work, Siyāsat-nāma (the Book of Government), is based on his political and governmental experiences, his understanding of Islamic doctrines, and Persian political traditions.